Jurisprudential analysis of the relationship between right and ruling - Mohamadbagher amerinia; Abasali Farahati (مطالعات فقه و حقوق اسلامی)
There is a difference of opinion about the nature of the right and ruling. Some have defined the right as domination, some have defined it as a type of property, and some have defined it as a special credit. This disorder has caused that there is a difference of opinion in determining the examples and recognizing the right from the verdict. In the famous view, whatever has the ability to be revoked or transferred is a right, and whatever lacks these three characteristics is a ruling. In spite of its reputation, this criterion requires vicious circle. This means that everything that can be revoked and transferred is considered a right, then the question arises as to what can be revoked or transferred. As when we say in the definition of the sentence; Ruling is something that cannot be revoked or transferred, the question comes to mind as to what cannot be revoked or transferred. Perhaps it can be said that a better criterion for identifying the right and ruling is to say that whatever is contrary to the public order from the point of view of jurisprudential and legal foundations will be a ruling and its opposite will be an example of right. Another issue that is important in the discussion of right and ruling is cases of doubt, that is, cases where there is doubt between whether they are right or ruling. In such cases, various solutions have been presented; Some people consider it preferable to be "right", while they consider being "ruling" as requiring a reason, and others the opposite, but it seems that in these cases, it is necessary to refer to other rules and principles, including practical principles, depending on the case.